Pesquisas acadêmicas brasileiras sobre a formação continuada do professor de Matemática: um enfoque nas práticas formativas - Lima, Hilda Ciriaco (Universidade Federal de São Carlos, 2018)
This research has as main objective to describe and analyze formative practices highlighted in research on continuing education of teachers of mathematics, to support each other both on the issue "guideline what the research on continuing education of math teacher show about training practices "? To this end we present relevant aspects initially on the training of these professionals, obtained from the mapping of the brazilian academic research on continuing education of teachers who teach mathematics in the period 2001-2016, which provides an overview of the productions. This was done from the search in two banks, a constant in the e-book mapping the brazilian academic research about the teacher who teaches math and another on Brazilian Digital Library of Theses and Dissertations, by combining two keywords "training continued " and " teachers who teach mathematics ". Later still, we present an overview on the Brazilian academic research on continuing education of specialist teacher in mathematics, that is, the teacher who teaches math in the final years of primary school and high school, which allowed us to analyze educational practices from the training contexts and its features, promoting a larger view of the information identified in such research. Qualitative in nature and state of the art, this survey has its bases in the Field of Teacher Education and Teacher Professional Development, (GARCIA, 1995, 1997, 1998, 2001, 2009); (IMBERNÓN, 2010); (NÓVOA, 2009); (COCHRAN-SMITH and LYTLE, 1999), including the Mathematics Education, (FIORENTINI, 2002, 2005, 2013, 2016); (MISKULIN, 2005); (PASSOS, 2005, 2016); (NACARATO, 2005, 2006, 2016); (PONTE, 2005), which also underlie our analyses. The main results show growth of thematic studies during the analysis period and indicate the contribution of all regions, however, are still concentrating on the Southeast. In mapping have a significant number of research on elementary school, 91 out of a total of 119 research mapped and there is demand for investigations into the teacher who teaches mathematics in Early Childhood Education, Adult and Youth Education and high school. The panorama of the 58 research on continuing education of specialist teacher, indicates that the thematic foci of higher analysis are training practices (76%), the data collection instruments used are questionnaires, interviews and observations, the nature of the 95% of the total research is qualitative and the most obvious types are action research, case study and exploratory. In relation to training practices, the review reveals partnerships between university and school or university and secretariats of education as a promising element of training and the university as a place formative actions prevalent. While we can observe the roles assumed by the participants are mostly well demarcated, in the preparation and development of the proposal and training activities attributable exclusively to the trainer, revealing a design close to the knowledge-to-the-practice. However, it is possible to envision some innovations concerning the planning set on the diagnosis of training needs and analysis and reflection on practice supported by a collaborative work.
Brazilian academic research on the continued training of mathematics teacher: a focus on training practices
Keywords: Formação continuada; Professores de matemática; Práticas formativas; Desenvolvimento profissional docente; Continuing Education; Math teachers; Training Practices; Teacher Professional Development.; CIENCIAS HUMANAS::EDUCACAO